Extensions of Ostrowski Type Inequalities via h-Integrals and s-Convexity - Khuram Ali Khan; Khalid Mahmood Awan; Allah Ditta; Ammara Nosheen; Rostin Mabela Matendo (Journal of Mathematics)
In this paper, Hölder, Minkowski, and power mean inequalities are used to establish Ostrowski type inequalities for s-convex functions via h-calculus. The new inequalities are generalized versions of Ostrowski type inequalities available in literature.